2022
DOI: 10.1021/acsinfecdis.1c00611
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Phosphonium Compounds: An Examination of Non-Nitrogenous Cationic Amphiphiles That Evade Disinfectant Resistance

Abstract: Quaternary ammonium compounds (QACs) serve as mainstays in the formulation of disinfectants and antiseptics. However, an over-reliance and misuse of our limited QAC arsenal has driven the development and spread of resistance to these compounds, as well as co-resistance to common antibiotics. Extensive use of these compounds throughout the COVID-19 pandemic thus raises concern for the accelerated proliferation of antimicrobial resistance and demands for next-generation antimicrobials with divergent architecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 74 publications
0
39
0
Order By: Relevance
“…This was circumvented by exposure to the desired alkyl bromide, which led to clean monoalkylation, followed by methylation with iodomethane to produce the corresponding bisQPC structures; this was accomplished for three compounds (Scheme 1C). Inspection of 31 P, 13 C, and 1 H NMR spectra of these P-2Z-P derived compounds indicated that the resulting products had isomerized to the E-alkenes; all 31 P resonances were observed at precisely 23.8 ppm, matching the P-2E-P derived bisQPCs. This isomerization would seemingly minimize the significant steric strain imposed by the four phenyl groups.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…This was circumvented by exposure to the desired alkyl bromide, which led to clean monoalkylation, followed by methylation with iodomethane to produce the corresponding bisQPC structures; this was accomplished for three compounds (Scheme 1C). Inspection of 31 P, 13 C, and 1 H NMR spectra of these P-2Z-P derived compounds indicated that the resulting products had isomerized to the E-alkenes; all 31 P resonances were observed at precisely 23.8 ppm, matching the P-2E-P derived bisQPCs. This isomerization would seemingly minimize the significant steric strain imposed by the four phenyl groups.…”
Section: Resultsmentioning
confidence: 92%
“…All yields refer to spectroscopically pure compounds. 1 H, 13 C, and 31 P NMR spectra were measured with a 400 MHz or 500 MHz JEOL spectrophotometer, and chemical shifts were reported on a δ-scale (ppm) downfield from TMS or 85 % H 3 PO 4 . Coupling constants were calculated in Hertz.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations